Proposta de validação de forma e constructo de um protocolo de avaliação acústica da deglutição - Martins, Barbara M. Madalozzo (2017)
Validated instruments are not frequent in the area of oropharyngeal dysphagia,specially in studies of swallowing(deglutition??) sounds through cervical auscultation. Therefore, this study is justified by the technical and scientific Scenario not only of the diagnosis of dysphagia, but also of the principles (or variables) that determine the therapeutic behaviors. The aim of this study was to elaborate and validate the form and content of an acoustic evaluation protocol for deglutition. Step 1 of the study was subdivided into a review of the literature to verify the frequency of the parameters; Analysis by an expert bank to select the parameters and assignment of the degree of importance for each parameter through a scale of 0 to 10. Step 1 was finalized with the elaboration of the first version of the protocol by the expert bank and structuring of its manual of application. Step 2 provided evidences of validity based on content through the evaluation and opinion of a committee composed of 5 judges with expertise in oropharyngeal dysphagia, as well as the analysis and compilation of the results by the specialist bank, culminating in the development of the second version of the protocol. In order to stratify judges' opinion, the Content Validity Index (CVI) was calculated, finding the percentage of agreement. In order to obtain the universal consensus, CVI-UA (universal agrément), the percentage of parameters and items with a CVI greater than 80% was calculated and the mean agreement (mean CVI) was also performed. At this stage, evidence of validity based on the response process was obtained through a structured tool developed by 5 speech therapists. The understanding and applicability of the questions were analyzed quantitatively and allowed the development of the second version of the protocol by the expert bank. The average of the degree of importance of the items in the opinion of the expert bank was 9.88. In Step 2, none of the items of the instrument obtained CVI less than 80% with total agreement, were found indexes greater than 95% of the total understanding of the content by the applicators, that considered of easy and practical application. It was possible to elaborate and validate in form and content of an acoustic evaluation protocol for swallowing(deglutition).